The effect of excessive coffee consumption, in relation to diterpenes levels of medium-roasted coffee, on non-high-density lipoprotein cholesterol level in healthy men - Awwad, Shady; Abu-Zaiton, Ahmed; Issa, Reem; Said, Rana; Sundookah, Ahmad; Habash, Maha; Mohammad, Beisan; Abu-Samak, Mahmoud (Farmacija, 2023)
This study was designed to determine the levels of coffee oil and diterpenes and evaluate the correlation between the effect of excessive roasted coffee consumption on non-high-density lipoprotein cholesterol (non-HDL) and the roasting degree effect on the levels of coffee oil and diterpenes extracted from Coffea arabica . The coffee oil and diterpenes were extracted using soxhlet and liquid-liquid extraction. Sixty-six healthy normolipidemic male participants were assigned for this study which consisted of two stages. The first stage is the coffee abstaining stage where subjects were requested to abstain from drinking coffee for 2 weeks. The second stage is the coffee drinking stage which consisted of groups (the control group and coffee-drinking group). The levels of TC, TG, LDL-C, HDL-C, and non-HDL were determined in all participants before and after the experiment. The results indicated that the coffee roasting degree demonstrated a significant increase in the levels of coffee oil and diterpenes ranging from 9.31% (green coffee) to 15.64% (dark roast) and from 0.205% (green coffee) to 0.300% (dark roast) for diterpenes. In conclusion, the current study revealed that excessive consumption of medium roasted coffee was associated with elevated non-HDL levels in normotensive nonsmoker healthy men which might be attributed to the positive association between the degree of roasting and diterpenes levels.